1997
DOI: 10.1038/sj.leu.2400685
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and practical considerations for the measurement of P-glycoprotein function in acute myeloid leukemia

Abstract: This paper summarizes experimental data and theoretical conare the level of sensitivity that is deemed relevant for the study The following discussion of detection methods will be in the Materials and methods cells.Keywords: P-glycoprotein; multidrug resistance; leukemia; PSC833; rhodamine 123All cell lines and treatment of AML samples and other methods have been extensively described in our earlier papers. 1-10 Additional specific details are given when considered Introduction useful, in the Results section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 7 publications
5
23
0
Order By: Relevance
“…14,16 This was confirmed in the present group of untreated AMLs (RHOratio vs DNRratio (n = 140): r s = 0.51, (P Ͻ 0.0001); RHOratio vs PGPMRK16 (n = 134): r s = 0.50, (P Ͻ 0.0001)). For this reason and the reasons discussed extensively before, 14,16 we regard the RHOratio parameter as the 'gold standard' for Pgp activity to which other parameters are compared. Eighty-seven percent of the RHOratio values were below 2.0 and 97% below 3.0.…”
Section: Pgp Activitysupporting
confidence: 70%
See 2 more Smart Citations
“…14,16 This was confirmed in the present group of untreated AMLs (RHOratio vs DNRratio (n = 140): r s = 0.51, (P Ͻ 0.0001); RHOratio vs PGPMRK16 (n = 134): r s = 0.50, (P Ͻ 0.0001)). For this reason and the reasons discussed extensively before, 14,16 we regard the RHOratio parameter as the 'gold standard' for Pgp activity to which other parameters are compared. Eighty-seven percent of the RHOratio values were below 2.0 and 97% below 3.0.…”
Section: Pgp Activitysupporting
confidence: 70%
“…14,16 SW-1573 and SW-1573/2R120, GLC 4 and GLC 4 /ADR lung carcinoma cell lines are used as controls for the detection of LRP and MRP1.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we compared a CLSM method for the quantification of nuclear-fixed SYTO16 with flow cytometric data. We have previously shown that the low sensitivity of daunorubicin as a P-gp probe precluded the accurate measurement of the PSC 833 effect in KB8 cells, as well as in most AML samples, by CLSM analysis of about 200 cells (Broxterman et al, 1997). Using SYTO16 in KB8 cells, the development of fluorescence in individual cells was first followed qualitatively in real time before and after the addition of PSC 833 and after fixation.…”
Section: Confocal Laser Scanning Microscopy Cell Linesmentioning
confidence: 99%
“…It is important to realize that, for any new combination of probe and modulator, one should be aware of putative interactions with the fluorescence of the probe not related to pump activity and appropriate controls have to be performed. We have discussed the theoretical and practical considerations of the different probes in a more comprehensive way in Broxterman et al (1997).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%